COMPARATIVE CLIMATIC CHARACTERISTICS BETWEEN THE WINTER OF 2011–2012 AND THE WINTER OF 1953–1954 IN THE SOUTH OF ROMANIA - ION MARINICĂ; ANDREEA FLORIANA MARINICĂ; OCTAVIA BOGDAN (Revue Roumaine de Géographie)
The authors makes a comparative analysis of the typical climatic evolution in two winter season: 2011–2012 and 1953–1954, the latter interval representing a 20th-century risk-high record. The beginning was January 25, 2012 when, after an excessively dry autumn, the weather would change all of a sudden. The first two warm winter months, which had lasted until January the 24th 2012, were followed by truewinter weather between January 25 and February 15, when temperatures dropped below -20°C, associated with heavy snowfalls, snowstorms and strong winds (70–80 km/h) that blew and drifted the snow with disastrous effects for Romania’s south-east counties, in particular. National losses: disrupted traffic of all types, snow-blocked households and animal shelters, black-outs, closed schools,difficulties in conducting supply and salvage operations for the population, etc. Although the harsh weather lasted only 25 days (blizzards, 40–135 cm-deep snow cover, 2–3 m-high snowpacks), yet the picture was partly similar to the 1953–1954 winter season which remains the severest one not only in the 20th century, but in the whole history of meteorological observations in Romania.